Perlindungan Hukum Terhadap Seseorang Yang Dipotret Tanpa Izin Untuk Kepentingan Komersial - Laurentius Ervin Ricky Pramudita , Laurentius Ervin Ricky Pramudita; Retno Dwi Pulung Sari , Retno Dwi Pulung Sari (Program Studi Magister Ilmu Hukum Universitas Islam Nusantara, 2024)
Copyright has exlusive rights within it wich are regulated in Undang-Undang Nomor 28 Tahun 2014 tentang Hak Cipta, namely Economic Rights and Moral Rights. Photography is a form of copyright that is protected by law. In the current digital era, photography copyright is a serious problem, so the government must implement these laws seriously. Taking portraits without permission and commercializing them is a form of violation committed by parties who do not bid to gain profit and cause losses to the actual owner of the copyright. With this, the author in his writing wants to know what harm is caused to someone who is photographed without permission for commercial purposes and also to know the legal consequences that arise from photographing people without permission for commercial purposes. This research was carried out using normative juridical research methods which used books, articles, and other legal materials as supporting sources for writing. This research focuses on the losses incurred by the objects in the portraits, giving rise to legal consequences in the form of copyright protection as regulated in law, namely economic rights and moral rights, as well as forms of compensation for losses suffered by the subjects used as portraits the commercialized portrait object.